Trichomonas Infection in a Community of Free-Ranging Domestic and Wild Columbiformes and Bonelli's Eagle (Aquila fasciata) - Santos, Nuno; Jambas, José; Monteiro, António; Amaral, Jorge; Martins, Nuno; Garcia, Javier; Fernández, Ana Martinez; Tyler, Kevin Morris; Almeida, Tereza; Abrantes, Joana; Esteves, Pedro J. (Frontiers in Veterinary Science, 2019)
Trichomonas spgallinae. is a pathogen of conservation relevance, whose main maintenance hosts are Columbiformes, but spillover to avian predators has been described. The goal of this study was to characterize the epidemiology of Trichomonas spp. in a community of free-ranging domestic and wild Columbiformes and an endangered predator, Bonelli’s eagle Aquila fasciata. We surveyed 253 live-captured Rock doves, 16 nestling Bonelli’s eagles and 41 hunted Columbiformes. Oro-esophageal swabs were incubated in culture media and Trichomonas spp. isolated from Bonelli’s eagle (6.3%, CI95 1.1-28.3), Turtle dove Streptopelia turtur (56.3%, CI95 39.3-71.8), Wood pigeon Columba palumbus (83.3%, CI95 43.7-97.0) and Rock dove Columba livia (68.4%, CI95 62.4-73.8). Infected Rock doves showed significantly poorer body condition than uninfected ones (p=0.022). From a subset of 32 isolates, 18S and ITS1/5.8S/ITS2 rRNA genes were sequenced and Maximum-Likelihood trees inferred. Four ribotypes of Trichomonas spp. were identified. In this study area Trichomonas spp. seem to persists in a multi-host system involving several species of Columbiformes. Conservation actions aimed at increasing the availability of trophic resources for Bonelli’s eagles through Rock dove restocking should consider the risk of pathogen transmission and of introduction of alien strains.